Feasibility and safety of elective laparoscopic total extraperitoneal preperitoneal groin hernia repair in the elderly: a propensity score-matched comparison - Liu YB (Dove Medical Press, 2018)
Ying-Buh Liu,1 Chih-Chin Yu,1 Chao-Chuan Wu,1,2 Chia-Da Lin,1,2 Shih-Chieh Chueh,3,4 Yao-Chou Tsai1,2 1Department of Surgery, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Taipei, Taiwan; 2Department of Urology, Tzu Chi University, Medical College, Hualien, Taiwan; 3Department of Urology, National Taiwan University Hospital, Taipei, Taiwan; 4Cleveland Clinic, Glickman Urologic and Kidney Institute, Cleveland Clinic Lerner College of Medicine, Cleveland, OH, USA Background: Several studies of hernia registries have revealed that elderly patients have higher perioperative complication rates compared with younger patients. However, the incidence of hernia increases with the aging process. To evaluate the feasibility and safety of laparoscopic hernia repair in elderly patients (≥75 years), we conducted a prospective case-matched control study to compare perioperative outcomes between patients older and younger than 75 years. Methods: Between September 2008 and July 2015, 572 consecutive patients undergoing endoscopic hernia repair were included in this prospective study. This case-matched control study was matched based on sex, American Society of Anesthesiologists score, and body mass index between patients younger and ≥75 years. The propensity-score matching of two groups was carried out on a 1:1 basis. Perioperative data were prospectively recorded for all patients including demographic data, operation time, length of hospital stay, narcotic dose, and complications. Results: In the final analysis, 54 patients who were <75 years were extracted to match the 54 patients ≥75 years. These two groups had similar baseline characteristics excluding age. They also had similar perioperative outcomes in hernia recurrence, metachronous contralateral hernia occurrence, complication rate and chronic pain. The patients ≥75 years of age had lower requirements for analgesics than those who were <75 years of age (p=0.047). Conclusion: This is the first comparative cohort study investigating the impact of aging in an Asian hernia population. Laparoscopic inguinal hernia repair is feasible and safe for older patients, with comparable perioperative outcomes to patients <75 years. Keywords: inguinal hernia, TEP, age, complication